2017
DOI: 10.1111/jocn.13784
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of aromatherapy massage among adult female cancer patients: A qualitative study

Abstract: Aromatherapy massage seems to have both physical and psychological benefits for women with cancer. The findings elucidated a wide range of benefits that are perceived in such complex intervention, and the contextual factors that may influence these perceived benefits. This will inform future nurse-led quantitative research in the clinical setting. The study highlights the importance of touch towards a caring relationship and the provision of cancer care with a gender-specific approach. Exploring of the lived e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
3
17
0
3
Order By: Relevance
“…Item scoring is done on a six-point Likert-type scale from 1 ("Strongly disagree") to 6 ("Strongly agree"). Items 2,4,7,11,13,14,15,18,19, and 22 -24 are scored reversely. The possible total scores of the physical, psychospiritual, social, and environmental dimensions and the total HCQ score are 5 -30, 10 -60, 4 -24, 5 -30, and 24 -144, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Item scoring is done on a six-point Likert-type scale from 1 ("Strongly disagree") to 6 ("Strongly agree"). Items 2,4,7,11,13,14,15,18,19, and 22 -24 are scored reversely. The possible total scores of the physical, psychospiritual, social, and environmental dimensions and the total HCQ score are 5 -30, 10 -60, 4 -24, 5 -30, and 24 -144, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It also promotes blood circulation and reduces peripheral edema (17,18). Previous studies reported the positive effects of massage on relaxation (12), comfort (18), pain, and physiological stability (15,17,19). Contrarily, some studies reported conflicting findings respecting the effects of massage.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical use and assessment of the potential benefits of the complementary therapies in the treatment of cancer patients has recently increased in both pediatric (18)(19)(20)(21)(22) and adult patients (23)(24)(25)(26) . Among the manipulation practices based on the body, the therapeutic massage stands out as the most commonly used complementary therapy modality (41)(42) .…”
Section: Discussionmentioning
confidence: 99%
“…As pesquisas que utilizaram a musicoterapia ou a massagem em pacientes oncológicos, seja durante o processo de quimioterapia (E27, E28), em grupo de autoajuda (E25) ou para a dor oncológica (E26), obtiveram como resultados uma diminuição na ansiedade (E27, E28), fadiga (E27) e dor (E26), e um aumento do bem-estar geral (E25) (HO et al, 2017;HUANG;GOOD;ZAUSZNIEWSKI, 2010;KARAGOZOGLU;KAHVE, 2013;LIN et al, 2011).…”
Section: Ações Assistenciais Do Enfermeiro Na Reabilitação Oncológicaunclassified
“…Do mesmo modo, a massagem terapêutica também pode se tornar um recurso importante ao enfermeiro em sua atuação na reabilitação oncológica. Um ensaio clínico revelou que a aplicação de massagem em pacientes atendidos no Instituto de Terapia Integrada e Oriental, reduziu sintomas de ansiedade, fadiga, dor e proporcionou relaxamento (KUREBAYASHI et al, 2016), como encontrado pelos estudos E25 e E27 desta RI (HO et al, 2017; KARAGOZOGLU; KAHVE, 2013).…”
Section: Ações Assistenciais Do Enfermeiro Na Reabilitação Oncológicaunclassified